Prevalence and Risk Factors of Anaplasmosis in Simmental Cattle in the Peruvian Amazon - Hugo Frias; Luis Murga; William Bardales; Vanessa Frias; Segundo Melecio Portocarrero-Villegas; Tatiana Segura Portocarrero; Miguel Arista; José Américo Saucedo-Uriarte (Veterinary Medicine International)
Anaplasmosis, transmitted biologically and mechanically, is one of the most prevalent diseases responsible for high production costs worldwide. In this research, the prevalence and risk factors of anaplasmosis in Simmental cattle raised in the Peruvian Amazon were evaluated. 266 blood samples were collected from bovines of different categories such as calves male, calves females, heifers <1.3 years, heifers >1.3 years, steers, bulls, and cows from the districts of Omia and Molinopampa. The enzyme-linked immunosorbent assay (ELISA) technique was used to detect antibodies against Anaplasma marginale. Of the 266 animals sampled, 67% were positive for A. marginale. A higher prevalence was determined in the district of Omia (99.3%), while in the district of Molinopampa, 28.7% was obtained. A prevalence of A. marginale was recorded in females (67.7%) and in males (64.8%) p>0.05. There is a significant association of the disease with the category of cattle, verifying the highest prevalence of A. marginale in calves male, heifer >1.3 years, and bull. The multiple correspondence analysis shows that San Mateo, Puma Marca, Mashuyacu, Primavera, and Los Olivos have a higher prevalence of anaplasmosis, associated with altitude of 1701–2000 m, spray baths and paddock rotation. Anaplasmosis is prevalent in Simmental cattle from the Peruvian Amazon, with a higher incidence in Omia and in females, considering May to August the critical months and the altitude less than 2000 meters above sea level.